Great Britain’s Stance Towards Political Changes in China in the Years 1908–1909 - Pajor, Jan (Instytut Historii Polskiej Akademii Nauk, 2023)
Between 1908 and 1909, significant political changes took place in China. Following the death of the nominal sovereign, Guangxu, and the Empress Dowager Cixi, who exercised real power, the minor Puyi was selected as the new emperor. The regency was assumed by the weak and inept Prince Chun, who dismissed the most influential imperial dignitary, Yuan Shikai, in early 1909. When the second major dignitary, Zhang Zidong, died shortly later, the Beijing authorities found themselves in crisis. The article shows how Great Britain, which had the strongest position among the powers in China, reacted to these developments.
s. 47-81
Keywords: Chiny -- stosunki -- Wielka Brytania [KABA]; Wielka Brytania -- stosunki -- Chiny [KABA]; Wielka Brytania -- stosunki zagraniczne -- 1870-1914 [KABA]; Grey of Fallodon, Edward Grey (1862-1933; viscount) [KABA]; Yuan, Shikai (1859-1916) [KABA]; Guangxu (1871-1908) [KABA]; Cixi (cesarzowa Chin; 1835-1908) [KABA]; Zhang Zhidong (1837-1909); Zaifeng, 2. książę Chun (1883-1951) - polityka i rządy